2008
DOI: 10.1007/s12291-008-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the hypoglycemic effect of Peganum harmala L. Seeds ethanol extract on normal and streptozotocin induced diabetic rats

Abstract: Peganum harmala L. (Zygophyllaceae) is a traditional medicine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Its different parts are used in folk medicine for the treatment of variety of human sicknesses such as lumbago, asthma, colic, jaundice and as a stimulant emmenagogue [1]. Several pharmacological activities such as anti-tumor, insecticidal and antimalarial effects [2], antileishmanial [3][4][5], anti-spasmodic, anti-histaminic, vasorelaxant effects [6], wound healing, antioxidant activity, immunomodulator properties leukemia healing [7], hypoglycemic effects [8], analgesic and anti-inflammatory properties, antinociceptive effects [9], antitumor activity [10], hepatoprotective effect [11], antibacterial, antifungal and antiviral effects and anti-ulcer activity [12] have been reported for this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Its different parts are used in folk medicine for the treatment of variety of human sicknesses such as lumbago, asthma, colic, jaundice and as a stimulant emmenagogue [1]. Several pharmacological activities such as anti-tumor, insecticidal and antimalarial effects [2], antileishmanial [3][4][5], anti-spasmodic, anti-histaminic, vasorelaxant effects [6], wound healing, antioxidant activity, immunomodulator properties leukemia healing [7], hypoglycemic effects [8], analgesic and anti-inflammatory properties, antinociceptive effects [9], antitumor activity [10], hepatoprotective effect [11], antibacterial, antifungal and antiviral effects and anti-ulcer activity [12] have been reported for this plant.…”
Section: Introductionmentioning
confidence: 99%
“…Decrease in total cholesterol by 100 mg/kg P. harmala was due to the inhibition of 3-hydroxy3methyl-glutaryl-CoA (HMGCoA) reductase by different alkaloids harmine, harmaline, and harmol present in P. harmala. These alkaloids have also been reported to have hypoglycemic properties (Singh et al, 2008). So, decrease in Level of Cholesterol in the other groups (200,400 mg/kg P. harmala) that have been associated with increased HMGCoA reductase enzyme levels may be due to the excretion of bile acids.…”
Section: Resultsmentioning
confidence: 97%
“…The medicinal properties of the plant P. harmala are mainly attributed to harmaline, harmine, harmalol, harmol and tetrahydroharmine, previously identified and quantified as the main beta-carboline alkaloids in P. harmala extracts. [10][11][12][13][14][15][16][17][18][19][20][21][22] Based on this report, the spasmolytic activity of the ethanol extract of P. harmala studied here may be attributed to these alkaloids. In summary, the current study indicated promising antispasmodic activity of P. harmal as a medicinal plant.…”
Section: % Contractilitymentioning
confidence: 96%
“…[7] In recent years, different pharmacological and therapeutic effects of P. harmala and its active alkaloids, especially harmine and harmaline have been demonstrated. [8] These effects include spontaneous effects on isolated rat uterus [9] anti-leishmanial, [10] anti-tumor effect, [11,12] insecticidal, [13] vasorelaxant effect [14,15] wound healing, anti-oxidant activity, [16] leukemic healing, [17] hypoglycemic effect, wound healing, anti-oxidant activity, [16] leukemic healing, [17] hypoglycemic effect, [18] immuno-modulator properties, [16] analgesic and anti-inflammatory properties, [19] antibacterial, antifungal and antiviral effects. [20,21] Recently, anti-secretory and cytoprotective effects have also been reported.…”
Section: Introductionmentioning
confidence: 99%